2008
DOI: 10.1016/j.dnarep.2007.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative damage recognition by UvrA and UvrB: Identification of UvrA residues that mediate DNA binding

Abstract: Nucleotide excision repair (NER) is responsible for the recognition and removal of numerous structurally unrelated DNA lesions. In prokaryotes, the proteins UvrA, UvrB and UvrC orchestrate the recognition and excision of aberrant lesions from DNA. Despite the progress we have made in understanding the NER pathway it remains unclear how the UvrA dimer interacts with DNA to facilitate DNA damage recognition. The purpose of this study was to define amino acids residues in UvrA that provide binding energy to DNA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 49 publications
4
27
0
Order By: Relevance
“…Fifty L1 nematodes were loaded into each well of a 96-well plate (4–6 wells per strain per treatment) using the COPAS Biosort. The volume of each well was then brought to 100μl with EPA H 2 O (Weber 1991), UVC-killed UvrA (UVC sensitive E. coli strain due to a lack of nucleotide excision repair (Croteau et al 2008)), and toxicant. With the exception of sodium arsenite (Ricca Chemical Company), all chemicals were purchased from Sigma-Aldrich (St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
“…Fifty L1 nematodes were loaded into each well of a 96-well plate (4–6 wells per strain per treatment) using the COPAS Biosort. The volume of each well was then brought to 100μl with EPA H 2 O (Weber 1991), UVC-killed UvrA (UVC sensitive E. coli strain due to a lack of nucleotide excision repair (Croteau et al 2008)), and toxicant. With the exception of sodium arsenite (Ricca Chemical Company), all chemicals were purchased from Sigma-Aldrich (St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
“…63,64 As shown by the E. coli UvrABC endonuclease that is involved in NER, the UvrA protein recognizes the DNA damage, and UvrB bends the DNA before the UvrB-UvrC complex catalyzes DNA backbone cleavage. 65,66 Similarly, SPL may have to team with other protein(s) for damage recognition and repair in vivo . These proteins would be missing in our in vitro studies, which may result in the low SPL activity observed.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, 1.5ml arsenite (0, 50, 250, 500μM) or AfB 1 (0, 5, 25, 50μM in 1% DMSO) was added to the surface of peptone-free, control or EtBr (1μg/ml) K-agar plates and allowed to dry. K-agar plates were then seeded with 300μl 20X concentrated UVC-killed UvrA bacteria (UV-sensitive strain, due to lack of NER [29]). Nematodes were transferred daily to freshly prepared plates.…”
Section: Methodsmentioning
confidence: 99%